Philosophical foundations of children's and family law - Brake, Elizabeth; Ferguson, Lucinda (Oxford : Oxford University Press, 2018)
This collection is the first of its kind to examine the ethical foundations of family law. Topics include the value of marriage, the scope of parental control rights, the protection of children's interests, and the role of religious freedom in the legal attitude to family relationships.
This edition previously issued in print: 2018.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on March 2, 2018).
Keywords: Domestic relations -- Moral and ethical aspects; Law; Laws of specific jurisdictions & specific areas of law